A comprehensive validation of the novel 8th edition of American Joint Committee on Cancer staging manual for the long-term survivals of patients with non-functional pancreatic neuroendocrine neoplasms. Issue 46 (13th November 2020) - Yang, Min; Zeng, Lin; Yao, Wen-Qing; Ke, Neng-wen; Tan, Chun-lu; Tian, Bo-le; Liu, Xu-bao; Xiang, Bo; Zhang, Yi
Abstract : Abstract: Histologically, the World Health Organization has classified pancreatic neuroendocrine neoplasms (p-NENs) into well-differentiated pancreatic neuroendocrine tumors (G1/G2 p-NETs) and poorly-differentiated pancreatic neuroendocrine carcinoma (G3 p-NECs) based on tumor mitotic counts and Ki-67 index. Recently, the 8th edition of American Joint Committee on Cancer (AJCC) tumor-node-metastasis (TNM) staging manual has incorporated some major changes in 2017 that the TNM staging system for p-NENs should only be applied to well-differentiated G1/G2 p-NETs, while poorly-differentiated G3 p-NECs be classified according to the new system for pancreatic exocrine adenocarcinomas. However, this new manual for p-NENs has seldom been evaluated. Data of patients with both G1/G2 and G3 non-functional p-NENs (NF-p-NENs) from our institution was retrospectively collected and analyzed using 2 new AJCC 8th staging systems. We also made survival comparisons between the 8th and 7th edition system separately for different subgroups. For G1/G2 NF-p-NETs, there were 52 patients classified in AJCC 8th edition stage I, 40 in stage II, 41 in stage III and 19 in stage IV. As for G3 NF-p-NECs, 17, 19, 24, and 18 patients were respectively defined from AJCC 8th edition stage I to stage IV. In terms of the AJCC 7th staging system, the 230 patients with NF-p-NENs were totally distributed from stage I to stage IV (94, 63, 36, 37, respectively). For the survival analysis of both G1/G2 NF-p-NETs and G3 NF-p-NECs, the AJCC 7th edition system failed to discriminate the survival differences when compared stage III with stage II or stage IV ( P  > .05), while the 8th edition ones could perfectly allocate patients into 4 statistically different groups ( P  < .05). The HCIs of AJCC 8th stage for G1/G2 NF-p-NETs [HCI=0.658, 95% confidence interval (CI)=0.602–0.741] and stage for G3 NF-p-NECs (HCI=0.704, 95% CI=0.595–0.813) was both statistically larger than those of AJCC 7th stage for different grading NF-p-NENs [(HCI=0.578, 95% CI=0.557–0.649; P =.031), (HCI=0.546, 95% CI=0.531–0.636; P  = .019); respectively], indicating a more accurate predictive ability for the survivals of NF-p-NENs. Our data suggested the 2 new AJCC 8th staging systems were superior to its 7th edition for patients with both G1/G2 NF-p-NETs and G3 NF-p-NECs. Abstract : Supplemental Digital Content is available in the text